Normative concentrations of urine thiocyanate in cassava eating communities in Nigeria. (14th August 2013) - Oluwole, O. S. A.; Oludiran, A. O.
Abstract: Exposure to cyanide is a major public health problem where highly cyanogenic cassava foods are consumed. Thiocyanate (SCN), the biomarker of exposure to cyanide is present in several foods, and produced endogenously. Concentrations of urine SCN were measured in endemic and non-endemic areas of ataxic polyneuropathy in Nigeria. Cassava food consumption in the endemic area was twice that of non-endemic areas. Geometrical mean (95% CI) urine SCN was 20 µmol/l (18–24) for no consumption of cassava foods, 56 µmol/l (49–64) for daily consumption, 56 µmol/l (48–65) for twice daily consumption and 85 µmol/l (62–117) for thrice daily consumption. 95th percentile reference limit was 125 µmol/l for no consumption of cassava food, but 360 µmol/l for thrice daily consumption. Urine SCN is a useful biomarker of exposure to cyanide from cassava foods. There is strong ecological association of exposure to cyanide and endemicity of ataxic polyneuropathy.